(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article examines communicative competence as a key outcome of foreign language education within the framework of competence-based learning. The study highlights the shift from knowledge-oriented approaches to communicative, learner-centered pedagogy in response to contemporary social, economic, and labor market demands. Communicative competence is analyzed as a multifaceted construct encompassing linguistic, sociolinguistic, pragmatic, cultural, and educational competencies. Particular attention is paid to the role of communicative language teaching and the Common European Framework of Reference for Languages (CEFR) in shaping modern foreign language instruction. The findings emphasize the necessity of integrating interactive, context-rich, and professionally oriented teaching practices to prepare learners for effective communication in academic and professional environments.